Stability of a flattened dipolar binary condensate: Emergence of the spin roton - Au-Chen Lee; D. Baillie; P. B. Blakie (Physical Review Research, 2022)
We develop a theory for a two-component miscible dipolar condensate in a planar trap. Using numerical solutions and a variational theory we solve for the excitation spectrum and identify regimes where density- and spin-roton excitations are favored. We characterize the various instabilities that can emerge in this system over a wide parameter regime and present results for the stability phase diagram. Importantly this allows us to identify the parameter regimes where a novel roton-immiscibility transition can occur, driven by the softening of the spin-roton excitation.